Efficacy of tailored recommendations to promote healthy lifestyles: a post hoc analysis of a randomized controlled trial. Issue 8 (10th April 2021) - Barroso, María; Zomeño, M Dolors; Díaz, Jorge L; Pérez, Silvia; Martí-Lluch, Ruth; Cordón, Ferran; Ramos, Rafel; Cabezas, Carmen; Salvador, Gemma; Castell, Conxa; Schröder, Helmut; Grau, María
Abstract: Prevention is the key to stopping the ravages of cardiovascular diseases, the main cause of death worldwide. The objective was to analyze the efficacy of tailored recommendations to promote healthy lifestyles. Parallel-arm randomized controlled trial with 1 year follow-up. Individuals aged 35–74 years from Girona (Spain) randomly selected from a population with no cardiovascular diseases at baseline were included. Participants in the intervention group received a brochure with tailored healthy choices according to the individual risk profile and a trained nurse explained all recommendations in detail in a 30 min consultation. One year changes in smoking, Mediterranean diet adherence, physical activity, and weight were analyzed with McNemar, Student's t, Wilcoxon, and Fisher exact tests according to an intention-to-treat strategy. Of 955 individuals (52.3% women; mean age 50 [±10] years) randomly allocated to the intervention or control group, one participant in each group presented a cardiovascular event and 768 (81%) were reexamined at 1 year follow-up. The prevalence of nonsmokers increased in both the intervention and control groups (78.1%–82.5%, p = <.001, and 76.7% to 78.8%, p = .015, respectively); however, significance persisted only in the intervention group when stratified by sex, age group, and educational level. Adherence to a Mediterranean diet increased in the intervention group (22.3%–26.5%, p = .048). In conclusion, a brief personalized intervention with science-based recommendations according to individual risk profiles appears to improve healthy lifestyles, particularly nonsmoking and adherence to a Mediterranean diet. This promising intervention system offers evidence-based recommendations to develop healthy lifestyles.